The Franciscan Prayer Elicits Empathic and Cooperative Intentions in Atheists: A Neurocognitive and Phenomenological Enquiry - Mercadillo, Roberto E.; Fernandez-Ruiz, Juan; Cadena, Omar; Domínguez-Salazar, Emilio; Pasaye, Erick H.; Velázquez-Moctezuma, Javier (Frontiers in Sociology, 2017)
Religiosity influences the alleviation of troubles through cooperative and empathic attitudes, but these involve a sense of community offered in non-religious support groups and healthcare institutions too, where individual’s spiritual wellbeing is based on responsibility and solidarity. This is the case of the Alcoholic Anonymous program adopted by several care initiatives, which use the Franciscan Prayer as a fundamental text representing a western epistemic meaning-making system to provide guidance for cooperation and empathy. We aimed to identify the effect of the Franciscan Prayer on the neurocognitive function and emotional-social experiences in 20 persons declared as atheist (M age = 22.85 ± 2.60 yr.). Spiritual profiles, acceptance of religion, and dispositional empathy were psychometrically evaluated. Functional images were acquired in a 3T scanner to identify BOLD signals while reading The Franciscan Prayer, The Lord’s Prayer representing a culturally known religious text with no Franciscan elements, and a birthday serenade representing a culturally known non-religious text. Phenomenological interviews were performed to categorize emotional experiences and social situations associated with reading each text. Results show that spiritual wellbeing and empathic dispositions are not allied with religious beliefs. The reading of The Franciscan Prayer was correlated with activation in primary motor and premotor cortices, parietal primary and integrative areas, and occipital primary and associative cortices. These motor and sensorial functions might be essential for the empathic attitudes expressed in the Franciscan tradition allowing cooperative actions. This is congruent with the participant’s experiences of wellness, reciprocity, responsibility and helping evoked by this prayer. The Lord's Prayer was correlated with activation in prefrontal regions, as well as, in anterior and posterior portions of the cingulate cortex. These activations may imply mnemonic and moral processes that may be needed for conflict valuations based on childhood and cultural memories evoked by the participants. As testimonies indicate, disgust, confusion, or criticisms were associated with the religious property of the text. We conclude that thoughts, emotions, and actions evoked by The Franciscan Prayer are not inclined by its religious quality but by its empathic and cooperative properties, which may allow for self-reflection and social actions needed for support groups.